Single Crystals Heterogeneity Impacts the Intrinsic and Extrinsic Properties of Metal–Organic Frameworks. Issue 3 (21st November 2021) - Fuchs, Adrian; Mannhardt, Petra; Hirschle, Patrick; Wang, Haoze; Zaytseva, Irina; Ji, Zhe; Yaghi, Omar; Wuttke, Stefan; Ploetz, Evelyn
Abstract: At present, an enormous characterization gap exists between the study of the crystal structure of a material and its bulk properties. Individual particles falling within this gap cannot be fully characterized in a correlative manner by current methods. The authors address this problem by exploiting the noninvasive nature of optical microscopy and spectroscopy for the correlative analysis of metal‐organic framework particles in situ. They probe the intrinsic as well as extrinsic properties in a correlated manner. The authors show that the crystal shape of MIL‐88A strongly impacts its optical absorption. Furthermore, the question of how homogeneously water is distributed and adsorbed within one of the most promising materials for harvesting water from humid air, MOF‐801, is addressed. The results demonstrate the considerable importance of the particle level and how it can affect the property of the material. Abstract : The influence of heterogeneities in metal–organic frameworks (MOFs) can be enormous at the single‐particle level but is often neglected in characterization due to the lack of microscopes capable of correlated studies on the same crystals. The authors present an analysis platform for correlated, in situ spectroscopy and imaging named MOSAIC, and unveil new heterogeneity–property relations for two important MOF systems.